2017
DOI: 10.17221/124/2016-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia and not hypoxia may reduce sperm motility and morphology following testicular hyperthermia

Abstract: ABSTRACT:The mammalian testis typically operates on the brink of hypoxia; the long-standing dogma is that increased testicular temperature increases metabolism, but blood flow is unaffected and the resulting hypoxia reduces sperm motility and morphology. In rats and mice, oxygen (O 2 ) content of inspired air affected O 2 content of testes, enabling the latter to range from approximately 50 to more than 200% of physiologic concentrations. A ram model was used to test the hypotheses that hypoxia would disrupt s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 33 publications
(47 reference statements)
2
11
0
1
Order By: Relevance
“…In conclusion, under acute hypoxic conditions (13% oxygen in inspired air), the testis maintained oxygen delivery and uptake by increasing blood flow and oxygen extraction, with no indications of a shift to anaerobic metabolism. Similarly, in our previous study in conscious rams, exposure of control rams (no scrotal insulation) to 85, 21 and 14% oxygen for 30 h had no significant effect on semen quality 13 . Thus, we concluded that the testis compensated for decreased oxygen concentrations in inspired air, although this needs additional confirmation.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In conclusion, under acute hypoxic conditions (13% oxygen in inspired air), the testis maintained oxygen delivery and uptake by increasing blood flow and oxygen extraction, with no indications of a shift to anaerobic metabolism. Similarly, in our previous study in conscious rams, exposure of control rams (no scrotal insulation) to 85, 21 and 14% oxygen for 30 h had no significant effect on semen quality 13 . Thus, we concluded that the testis compensated for decreased oxygen concentrations in inspired air, although this needs additional confirmation.…”
Section: Discussionsupporting
confidence: 67%
“…Although hyperemia was reported when testes not covered by the scrotum were exposed to increased temperatures 12 , this was not regarded as sufficient evidence to challenge the classical view that hypoxia mediates damage caused by testicular hyperthermia. In a previous preliminary study 13 , conscious rams breathed inspired air containing 85, 21 or 14% oxygen for 30 h. Half of the rams had an insulated scrotum (a well-established model to increase testicular temperature); in those rams, percentages of morphologically normal sperm and motile sperm were significantly decreased from ~2 to 5 wk after exposure. Furthermore, in that study, hyperoxia did not mitigate effects of scrotal insulation, nor did hypoxia cause subsequent decreases in morphologically normal or motile sperm.…”
Section: Introductionmentioning
confidence: 97%
“…It is known that the thermoregulation mechanisms of the male reproductive organ are not totally efficient (Losano et al, 2018). In the case of thermal stress, the increase in scrotal/testicular temperature occurs, thereby increasing cellular metabolism in the testicles, which leads to a higher O 2 need (Kastelic, Wilde, Rizzoto, & Thundathil, 2017). Testicular blood supply is limited and will not be enough to supply the increase in O 2 demand in testicular cells, which leads to cell death and testicular degeneration, affecting both spermatogenesis and androgenesis (Paul, Teng, & Saunders, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Em humanos e em animais de produção, para que a espermatogênese ocorra de maneira ideal é necessário que a temperatura testicular esteja de 2 a 6º C abaixo da temperatura corporal ALVES et al, 2016a), o que se denomina de termorregulação testicular. Embora a etiopatogenia da degeneração testicular tenha sido questionada recentemente (KASTELIC et al, 2017), até o momento acredita-se que a perda da termorregulação testicular, ocasionada pelo aumento da temperatura testicular, ocasiona aumento do metabolismo celular sem aumento na oxigenação testicular levando à hipóxia (PAUL et al, 2008;TENG;SAUNDERS, 2009). Essa condição resultará em estresse oxidativo das células presentes no epitélio seminífero, o que pode levar a prejuízos na qualidade espermática como queda de motilidade, aumento da porcentagem de espermatozoides anormais, danos ao DNA espermático e diminuição na concentração sérica de testosterona (ALVES et al, 2015(ALVES et al, , 2016a.…”
Section: Discussionunclassified